Combining ability of maize genotypes for fall armyworm (Spodoptera frugiperda J.E. Smith) resistance, yield and yield-related traits. (November 2021) - Kasoma, Chapwa; Shimelis, Hussein; Laing, Mark D.; Shayanowako, Admire; Mathew, Isack
Abstract: This study aimed to select desirable parents and single-cross hybrids with partial FAW resistance and suitable agronomic traits for effective (FAW) ( Spodoptera frugiperda Lepidoptera: Noctuidae J.E. Smith) resistance pre-breeding and breeding programs in Zambia and related agro-ecologies. A line × tester mating design was used to generate 60 experimental hybrids. The hybrids and their parents were evaluated in the field in three FAW hotspot locations in Zambia. Both the general and specific combining ability effects were significant (p < 0.05) for the assessed traits. Non-additive genetic effects were more important for the inheritance of grain yield and FAW-inflicted leaf and cob damage, suggesting that heterosis breeding would be the best strategy for improving these traits in this population. The narrow sense heritability (h 2 ) estimates for agronomic and FAW-related traits ranged from 0.14 to 0.47 and 0.37 to 0.49, respectively. The experimental hybrids CML346/EBL16469, ZM4236/CML545-B, CML346/CZL1310c, CML334/EBL173782, CML545-B/EBL169550 were among those selected with favourable specific combining ability estimates for grain yield, days-to-50 % anthesis, days-to-50 % silking, FAW leaf and cob damage resistance, respectively. The selected experimental hybrids are recommended for further evaluation and breeding in Zambia or similar agro-ecologies. Highlights: The fall armyworm (FAW) has established resident populations in SSA Sixty experimental hybrids were evaluated under natural FAW infestation in three sites General and specific combining ability (GCA and SCA) effects were significant in the inheritance of FAW resistance Favourable heritability estimates indicate prospects from improving FAW resistance in maize Experimental hybrids such as CML346/EBL16469, CML334/EBL173782 and CML545/EBL169550 ha favourable combining ability for grain yield, FAW leaf and cob damage, respectively Promising hybrids will be further evaluated for FAW and agronomic traits and advanced for breeding